New impulses from international development for more comprehensive and balanced public engagement evaluation. (13th December 2019) - Haenssgen, Marco J.
ABSTRACT: Public engagement in health research has gained popularity because of its potential to co-create knowledge, generate dialogue, and ground research in the priorities and realities of the target groups. However, public engagement that achieves these objectives could still entail unforeseen negative consequences or a wasteful use of resources. Although the evaluation of public engagement has evolved in recent years, we lack consistent evaluation criteria for systematic and transparent assessments of success and failure. This article introduces standard evaluation criteria from the field of development aid evaluation (effectiveness, efficiency, impact, relevance, sustainability) to promote more systematic and comprehensive evaluation practice. I apply these criteria to the public engagement component of a recent research project into antimicrobial resistance, antibiotic use, and health behaviour in Thailand and Laos. Considering village-level engagement workshops, international exhibitions of photo narratives of traditional healing in northern Thailand, and social media communication, I demonstrate that activities that seem to achieve their objectives can still have problematic characteristics in other dimensions. I conclude that these five generic evaluation criteria can broaden our understanding of public engagement. Their more widespread use in evaluations can help build a more comprehensive and balanced evidence base, even if only a sample of public engagement projects and programmes can be evaluated systematically.